Comparison Between Hydroplasty and Intra-articular Steroid Injection in Treatment of Idiopathic Frozen Shoulder - Dhungana, DP; Lamichhane, AP; Mahara, DP (Journal of Institute of Medicine Nepal, 2014)
Introduction: Idiopathic frozen shoulder is one of the common problems in orthopedic outpatient department. It is characterized by gradually progressive pain and stiffness of the shoulder followed by spontaneous recovery over the period of time.Many different modalities are available for the treatment of Idiopathic frozen shoulder, but no one is universally accepted. The purpose of this study was to compare the outcome of hydroplasty with intra-articular steroid injection. Methods: This was a comparative hospital based study conducted between March2011 to September2012, which included 50 patients with Idiopathic Frozen shoulder. There were 25 patients in each group. The mean age of respondent was 57.36 years. Simple Random method of sampling was adopted for selecting patients for each group. Hydroplasty group was given 30ml chilled(cold) sterile normal saline with 2 ml Methylprednisolone (80 mg), 4 ml 2% Lidocain(plain) and 4 ml 0.5% Bupivacain (total volume:40ml) and steroid group was given 2ml Methylprednisolone, 4ml 2% Lidocain(pain), 4ml 0.5% Bupivacain with total volume: 10 ml. Both groups were attached for therapeutic exercises. Comparison of outcomes between two treatment groups was done using Visual Analogue Scale (VAS) for pain, Shoulder Pain and Disability Index for Shoulder function and degree of range of motion. Statistical analysis was done using SPSS 17.0 Results: There was significant improvement in level of pain, Shoulder function (Shoulder Pain and Disability Index) and range of motion in forward flexion, abduction, external rotation, and internal rotation in three month period in Hydroplasty group compared to Steroid group. Conclusion: There was improvement in pain, range of movement and Shoulder Pain and Disability Index (SPADI) score in all patients of both group but the difference in improvement was found to be statistically significant in hydroplasty group as compared to steroid injection group. So Shoulder hydroplasty technique was found to be more effective treatment modality than intra-articular steroid injection in idiopathic frozen shoulder.